2019
DOI: 10.18203/2320-6012.ijrms20192541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respiratory morbidity among loading and unloading workers exposed to cement dust

Abstract: Background: A higher incidence of occupational diseases has been reported recently compared to the past years. One of the industries where workers are remarkably exposed to dust is cement industry. Several studies have been conducted to evaluate pulmonary functions and biochemical parameters of workers exposed to cement dust in factories and construction sites, but few were concentrated among loading and unloading workers of warehouses. Hence the present study was undertaken to find out the effect of cement du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Iraq and Aljeesh et al 22 in Palestine found comparable results for FEV 1 and FEV 1 /FVC, but not for FVC, which showed no significant differences between the two studied groups. By contrast, the findings of Neghab and Choobineh 3 and Krishna et al 23 in Iran agreed with the observations of Meo et al 24 in Pakistan that cementexposed workers had a significant reduction in FVC and FEV 1 but not FEV 1 /FVC. Mahmood et al 25 in Iraq with two studies conducted in Iran by Omidianidost et al 26 and Rafeemanesh et al 27 reported no significant differences in the spirometric parameters between workers and controls.…”
Section: Discussionsupporting
confidence: 79%
“…Iraq and Aljeesh et al 22 in Palestine found comparable results for FEV 1 and FEV 1 /FVC, but not for FVC, which showed no significant differences between the two studied groups. By contrast, the findings of Neghab and Choobineh 3 and Krishna et al 23 in Iran agreed with the observations of Meo et al 24 in Pakistan that cementexposed workers had a significant reduction in FVC and FEV 1 but not FEV 1 /FVC. Mahmood et al 25 in Iraq with two studies conducted in Iran by Omidianidost et al 26 and Rafeemanesh et al 27 reported no significant differences in the spirometric parameters between workers and controls.…”
Section: Discussionsupporting
confidence: 79%
“…The main route of entry of this dust is through inhalation (respiratory system) and swallowing (digestive system). 3,4 Cement as a whole, and its components are considered chemical hazards; excess amounts of these elements are potentially harmful to the biotic and abiotic components of the environment. 5 Microelements in cements, eg, chromium, are considered carcinogenic in 1980's.…”
mentioning
confidence: 99%
“…But the cement manufacturing projects are considered as major source of air pollution due to different hazardous emissions 5 . People are exposed to cement during its production, transportation or construction site 6 . Occupational airborne diseases are considered as one of the important cause of death and disability among people 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Occupational airborne diseases are considered as one of the important cause of death and disability among people 7 . Per year more than 2.3 million deaths occur due occupational illnesses 6 . Cement is a light gray powder which diameter is ranged between 0.05 to 5.0 µm.…”
Section: Introductionmentioning
confidence: 99%